2020
DOI: 10.1186/s12936-020-03231-7
|View full text |Cite
|
Sign up to set email alerts
|

The potential of anti-malarial compounds derived from African medicinal plants: a review of pharmacological evaluations from 2013 to 2019

Abstract: Background African Traditional Medicine (ATM) is used for the healthcare of about 80% of the rural populations of the continent of Africa. The practices of ATM make use of plant-products, which are known to contain plant-based secondary metabolites or natural products (NPs), likely to play key roles in drug discovery, particularly as lead compounds. For various reasons, including resistance of strains of Plasmodium to known anti-malarial drugs, local African populations often resort to plant-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 108 publications
4
36
0
4
Order By: Relevance
“…(Bello et al, 2017 ). Indeed, promising lead compounds have been identified from some of these plants (Amoa Onguéné et al, 2013 ; Ntie-Kang et al, 2014 ; Bekono et al, 2020 ). However, due to research and resource limitations, the active principles of too many extracts from Nigerian medicinal plants remain unknown, and further studies that would facilitate the translation of the few identified compounds into drug candidates are limited by a lack of funding for such work (Ebiloma et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“…(Bello et al, 2017 ). Indeed, promising lead compounds have been identified from some of these plants (Amoa Onguéné et al, 2013 ; Ntie-Kang et al, 2014 ; Bekono et al, 2020 ). However, due to research and resource limitations, the active principles of too many extracts from Nigerian medicinal plants remain unknown, and further studies that would facilitate the translation of the few identified compounds into drug candidates are limited by a lack of funding for such work (Ebiloma et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical screening result showed that the leaf latex of Aloe weloensis contained secondary metabolites ( avonoids, phenols, terpenoids, glycosides and others) which showed antimalarial activity in different plants extracts through various mechanism of action (14,22,23,31). Therefore, the antimalarial and antioxidant activities of Aloe weloensis could elicit from single or synergetic action of these metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Nature has gifted a variety of plants having potential effect against plasmodium parasites (12)(13)(14). Medicinal plants are the major resource for the treatment of malaria infections in Africa since health care facilities are limited (15).…”
Section: Introductionmentioning
confidence: 99%
“…Developing noble anti-malarial agents is imperative to overcome the challenges posed by the development of anti-malarial drug resistance. Nature has gifted various plants with a potential effect against plasmodium parasites [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The leaf latex Aloe weloensis showed a signi cant anti-malarial effect in 'Peter's (4-day suppressive) test and safe at 2000 mg/kg [16]. The leaf latex of this plant contains avonoids, glycosides, anthraquinones, saponins, terpenoids, and tannins that showed prominent anti-malarial activities in various plant extracts through a various mechanisms of action [12,[17][18][19]. This study was aimed to investigate the anti-malarial activity of the leaf latex of A. weloensis against Plasmodium parasites.…”
Section: Introductionmentioning
confidence: 99%